Experimental Hyperthyroidism Decreases Gene Expression and Serum Levels of Adipokines in Obesity - Renata de Azevedo Melo Luvizotto; André Ferreira do Nascimento; Maria Teresa de Síbio; Regiane Marques Castro Olímpio; Sandro José Conde; Ana Paula Lima-Leopoldo; André Soares Leopoldo; Antonio Carlos Cicogna; Célia Regina Nogueira (The Scientific World Journal)
Aims. To analyze the influence of hyperthyroidism on the gene expression and serum concentration of leptin, resistin, and adiponectin in obese animals. Main Methods. Male Wistar rats were randomly divided into two groups: control (C)—fed with commercial chow ad libitum—and obese (OB)—fed with a hypercaloric diet. After group characterization, the OB rats continued receiving a hypercaloric diet and were randomized into two groups: obese animals (OB) and obese with 25 μg triiodothyronine (T3)/100 BW (OT). The T3 dose was administered every day for the last 2 weeks of the study. After 30 weeks the animals were euthanized. Samples of blood and adipose tissue were collected for biochemical and hormonal analyses as well as gene expression of leptin, resistin, and adiponectin. Results. T3 treatment was effective, increasing fT3 levels and decreasing fT4 and TSH serum concentration. Administration of T3 promotes weight loss, decreases all fat deposits, and diminishes serum levels of leptin, resistin, and adiponectin by reducing their gene expression. Conclusions. Our results suggest that T3 modulate serum and gene expression levels of leptin, resistin, and adiponectin in experimental model of obesity, providing new insights regarding the relationship between T3 and adipokines in obesity.